Self-reported impulsivity, but not behavioral choice or response impulsivity, partially mediates the effect of stress on drinking behavior - HAMILTON, KRISTEN R. (2012)
Stress and impulsivity contribute to alcohol use, and stress may also act via impulsivity to increase drinking behavior. Impulsivity represents a multi-faceted construct and self-report and behavioral assessments may effectively capture distinct clinically relevant factors. The present research investigated whether aspects of impulsivity mediate the effect of stress on alcohol use. A community-based sample of 192 men and women was assessed on measures of cumulative stress, alcohol use, self-reported impulsivity, and behavioral choice and response impulsivity. Data were analyzed using regression and bootstrapping techniques to estimate indirect effects of stress on drinking via impulsivity. Cumulative adversity exhibited both direct effects and indirect effects (via self-reported impulsivity) on drinking behavior. Additional models examining specific types of stress indicated direct and indirect effects of trauma and recent life events, and indirect effects of major life events and chronic stressors on drinking behavior. Overall, cumulative stress was associated with increased drinking behavior, and this effect was partially mediated by self-reported impulsivity. Self-reported impulsivity also mediated the effects of different types of stress on drinking behavior. These findings highlight the value of mediation models to examine the pathways through which different types of stress increase drinking behavior. Treatment and prevention strategies should focus on enhancing stress management and self-control.